Operating mechanism and molecular dynamics of pheromone-binding protein ASP1 as influenced by pH. - Lei Han (PLoS ONE, 2014)
Odorant binding protein (OBP) is a vital component of the olfactory sensation system. It performs the specific role of ferrying odorant molecules to odorant receptors. OBP helps insects and types of animal to sense and transport stimuli molecules. However, the molecular details about how OBPs bind or release its odorant ligands are unclear. For some OBPs, the systems' pH level is reported to impact on the ligands' binding or unbinding capability. In this work we investigated the operating mechanism and molecular dynamics in bee antennal pheromone-binding protein ASP1 under varying pH conditions. We found that conformational flexibility is the key factor for regulating the interaction of ASP1 and its ligands, and the odorant binds to ASP1 at low pH conditions. Dynamics, once triggered by pH changes, play the key roles in coupling the global conformational changes with the odorant release. In ASP1, the C-terminus, the N-terminus, helix α2 and the region ranging from helices α4 to α5 form a cavity with a novel 'entrance' of binding. These are the major regions that respond to pH change and regulate the ligand release. Clearly there are processes of dynamics and hydrogen bond network propagation in ASP1 in response to pH stimuli. These findings lead to an understanding of the mechanism and dynamics of odorant-OBP interaction in OBP, and will benefit chemsensory-related biotech and agriculture research and development.